Ginger polysaccharide UGP1 suppressed human colon cancer growth via p53, Bax/Bcl-2, caspase-3 pathways and immunomodulation - Yanfang Qian; Chenying Shi; Chen Cheng; Dengwei Liao; Junping Liu; Gui-tang Chen (Food Science and Human Wellness)
In previous study, we got a purified ginger polysaccharide UGP1 and verified its significant antitumor activities on colon cancer HCT116 cells. In this article, we aimed to illustrate the underlying mechanism of UGP1 exerted antitumor activities on colon cancer by using in vitro cell models and in vivo animal models. The results demonstrated that UGP1 could induce S-phase cell cycle arrest, up-regulate the expression of Bax and p53, down-regulate the expression of Bcl-2, and activate the downstream protein caspase-9 and caspase-3, which was related to intrinsic apoptosis pathway on HCT116 cells. Moreover, UGP1 significantly stimulated RAW264.7 cell proliferation and secretion activity. Similarly, UGP1 inhibited tumor proliferation on tumor-bearing mice, increased the expression of p53 and the ratio of Bax/Bcl-2, enhanced the secretion of pro-inflammatory cytokines TNF-α, IL-2, IL-6 and decreased the secretion of pro-tumor cytokines TGF-β and bFGF in serum. In conclusion, it indicated that the UGP1 could suppress human colon cancer growth by inducing apoptosis via the regulation of p53, caspase-3, and Bax/Bcl-2 ratio-dependent pathway and regulating immune system activity. This investigation provided basic theoretical mechanism of ginger polysaccharide-exerted antitumor activities, and contributed to develop a possible functional food or adjuvant agent for prevention or treatment of colon cancer.